Perceptions Sociales De L’hygiene Et De L’assainissement En Milieu Urbain Et Rural Ivoirien - Nicolas, Brou Ahossi; Severin, Kouassi N’dri; Ai Modestine, Kadjo; Mel Joachim, Atchori; Jonas, Ibo Guéhi (European Scientific Journal, ESJ, 2018)
People’s perceptions of hygiene and sanitation appear to differ by community. Often, these perceptions do not contribute to improving the living conditions of the populations concerned. The study aims to improve hygiene and sanitation intervention strategies by better controlling people’s perceptions and behaviors. The aim is to assess the knowledge, attitudes and practices of populations according to gender as well as the perceptions of urban and rural populations in terms of hygiene and sanitation. Qualitative and quantitative approaches were used. Direct observation, individual interviews, focus groups and household survey are the main techniques used. Six (6) towns and six (6) villages in Côte d’Ivoire have been selected. The results demonstrate the similarity of perceptions and behaviors related to hygiene and sanitation. However, there is a variety of designations of their material and immaterial components. It does not reflect a variation of perceptions and behaviors, which would be linked to their original cultural substratum, but the differential effort of local populations in the context of adaptation to an existential environment. If cultural references do not support the hypothesis that "the perceptions and behaviors that people have in terms of hygiene and sanitation are determined by their cultural values, their socio-economic status and space in which they evolve ", the relations of the gender (women, men, children, notability, etc.) play a preponderant role in the determination of the perceptions and the behaviors for the improvement of the frameworks of life.